2015
DOI: 10.1177/0959683615591357
|View full text |Cite
|
Sign up to set email alerts
|

Decadal-resolution record of winter monsoon intensity over the last two millennia from planktic foraminiferal assemblages in the northeastern Arabian Sea

Abstract: The Indian monsoon system is an important climate feature of the northern Indian Ocean. Small variations of the wind and precipitation patterns have fundamental influence on the societal, agricultural, and economic development of India and its neighboring countries. To understand current trends, sensitivity to forcing, or natural variation, records beyond the instrumental period are needed. However, high-resolution archives of past winter monsoon variability are scarce. One potential archive of such records ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 88 publications
6
25
0
Order By: Relevance
“…TEX 86 -and alkenone-based SST reconstructions of cores NIOP905 and SO42-KL74 were shown to differ in magnitude and phase as TEX 86 temperature reconstructions seem to have a SW monsoon bias (Huguet et al, 2006). Munz et al (2015) showed that winter temper-atures derived from planktic foraminiferal assemblages had stronger amplitudes than the alkenone-based annual average SST reconstructions in SO130-275KL of Böll et al (2014). Two of the records used in this study have both, alkenone and Mg / Ca temperature.…”
Section: Integration and Averaging Of Sst And δ 15 N Reconstructionsmentioning
confidence: 93%
“…TEX 86 -and alkenone-based SST reconstructions of cores NIOP905 and SO42-KL74 were shown to differ in magnitude and phase as TEX 86 temperature reconstructions seem to have a SW monsoon bias (Huguet et al, 2006). Munz et al (2015) showed that winter temper-atures derived from planktic foraminiferal assemblages had stronger amplitudes than the alkenone-based annual average SST reconstructions in SO130-275KL of Böll et al (2014). Two of the records used in this study have both, alkenone and Mg / Ca temperature.…”
Section: Integration and Averaging Of Sst And δ 15 N Reconstructionsmentioning
confidence: 93%
“…The alongshore surface currents induce an offshore-directed deflection of surface waters and an upwelling of deeper, cold and nutrient-rich subsurface waters through the process of Ekman pumping. During boreal winter (December-March), weaker, dry and cold northeasterly winds (IWM, Indian winter monsoon) lead to increased surface water cooling and evaporation, especially in the northeastern part of the basin, where the IWM enables deep convective mixing and a second productivity peak during winter (Madhupratap et al, 1996;Schulz et al, 2002;Munz et al, 2015. Enhanced nutrient availability during summer upwelling nourishes primary productivity within the photic zone near the Somali and Omani coasts.…”
Section: Modern Oceanographic Settingmentioning
confidence: 99%
“…• N and 33 to 119 • E recently compiled by Munz et al (2015). To enhance the signal-to-noise ratio, rare species with < 0.5 % average abundance were removed from the calibration dataset prior to further analyses (Kucera et al, 2005), which resulted in the exclusion of 16 rare species out of 33 taxa.…”
Section: Planktic Foraminiferal Faunal Analyses and Transfer Functionmentioning
confidence: 99%
See 2 more Smart Citations